2023
DOI: 10.1002/slct.202203317
|View full text |Cite
|
Sign up to set email alerts
|

An Amino Acid‐Based Thixotropic Hydrogel: Tuning of Gel Recovery Time by Mechanical Shaking

Abstract: Fmoc-Trp-OH (Fmoc: N-fluorenylmethoxycarbonyl; Trp-OH: L-Tryptophan) undergone hydrogelation at 50 mM phosphate buffer saline of pH 7.4 with a minimum gelation concentration (MGC) of 0.25 % w/v after 12 to 15 hours. However, the hydrogel formation kinetics can be faster just by mechanical hand shaking of the hydrogelator solution during the hydrogel preparation procedure. The shake hydrogel is thermally and mechanically more stable than the non-shake hydrogel. These hydrogels have been characterized thoroughly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The blue shifts upon dilution were observed for all the hydrogels due to less scattering from their lower-order aggregates compared to the hydrogels. 4 The λ max peak at 303 nm for the native hydrogel Nap-F was red shifted to 315 nm/317 nm for the histidine-based two-component ( Nap-F H ), three-component ( Nap-F H–K and Nap-F H–R ) and four-component ( Nap-F H–K–R ) hydrogels. This could be due to the presence of π–π stacking interactions between the histidine aromatic imidazole side chain unit and phenyl aromatic moiety of the native gelator ( Nap-F ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The blue shifts upon dilution were observed for all the hydrogels due to less scattering from their lower-order aggregates compared to the hydrogels. 4 The λ max peak at 303 nm for the native hydrogel Nap-F was red shifted to 315 nm/317 nm for the histidine-based two-component ( Nap-F H ), three-component ( Nap-F H–K and Nap-F H–R ) and four-component ( Nap-F H–K–R ) hydrogels. This could be due to the presence of π–π stacking interactions between the histidine aromatic imidazole side chain unit and phenyl aromatic moiety of the native gelator ( Nap-F ).…”
Section: Resultsmentioning
confidence: 96%
“…This motivates us to study the hydrogelation behaviour of 1-naphthaleneacetic acid-conjugated phenylalanine ( Nap-F ) and hydrogelation behavior of its two-, three- and four-component systems. These systems have designed and developed judiciously by selecting the basic amino acids and Nap-F at various combinations as phenylalanine 4,20 is well known for its assembly propensity and basic amino acids are well known for their esterase-like activity in various peptides and proteins. 32,33 , 38,39 No catalytic activity has been identified from the native hydrogel ( Nap-F ) nor its diluted self-assembled solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gour et al reported the self-assembly of the nonaromatic amino acids cysteine (Cys) and methionine (Met) into amyloid-like fibrils in neutral water . The formation of amyloid-like assembled structures was verified by binding assays of Thioflavin T (ThT) and Congo red (CR) as ThT exhibited significant fluorescence enhancement, while CR showed increased red-shifted light absorption intensity upon binding to the amyloid structures. , In addition, amino acids could self-assemble into 3D gels through molecular modification. , Typically, Fmoc-modified amino acids are able to trap solvent molecules to form hydrogels. , Among these, as a leading hydrogel promoter, Fmoc-Phe has excellent assembly capabilities and could self-assemble into efficient, stable, and transparent hydrogels with a minimum gelation concentration of 0.1% w/v. Hydrogels with 3D structures act as templates to complex with silver ions (Ag + ) and induce the formation of silver nanoclusters in the presence of diffuse sunlight at pH 7.46 and room temperature .…”
Section: Assembly Mechanism Of Amino Acid Based Materialsmentioning
confidence: 99%
“…Such visual detection techniques are simple, convenient, and do not require major instruments. This gelation-based method has been utilised for the detection of different analytes such as metal ions, 26 sugars, 27,28 amino acids, 29,30 enzymes, 31,32 anions, 33,34 and others. 35,36 It is well known that anions play important roles in a wide range of chemical and biological processes.…”
Section: Introductionmentioning
confidence: 99%